The secret life of pronouns : what our words say about us - Pennebaker, James W. (New York : Bloomsbury Press, 2011)
Draws on groundbreaking research in computational linguistics to explain what language choices reveal about feelings, self-concept, and social intelligence, in a lighthearted treatise that also explores the language personalities of famous individuals.
Discovering the secret life of the most forgettable words -- Ignoring the content, celebrating the style -- The words of sex, age, and power -- Personality : finding the person within -- Emotion detection -- Lying words -- The language of status, power, and leadership -- The language of love -- Seeing groups, companies, and communities through their words -- Word sleuthing -- Appendix : A handy guide for spotting and interpreting function words in the wild.
Includes bibliographical references (p. 319-333) and index.
Keywords: English language -- Pronoun; English language -- Grammar; English language -- Pronoun; English language -- Grammar